Pengaruh Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan D’zalsya Cosmetik Marisa Kabupaten Pohuwato - Monoarfa , Sulerski; Sulaiman (Melati Institute, 2023)
This study aims to examine the effect of promotion and service quality on customer satisfaction of D'zalsya Cosmetik Marisa, Pohuwato Regency. Data collection techniques in this study through observation, interviews and questionnaires. This study uses (independent) variables consisting of Promotion (X1), Service Quality (X2) and the (dependent) variable is Customer Satisfaction (Y). The data was analyzed using multiple regression.The results of the study show multiple regression analysis, namely the formula Y = a + b1 x1 + b2 x2 (Y = 12,490 + 0.109 X1 + 0.67 X2). The T test results show that for the promotion variable X1 has a positive and insignificant effect on customer satisfaction, the service quality variable X2 has a positive and significant effect on customer satisfaction. The results of the F test show that the variables together (simultaneously) have a positive and significant effect on customer satisfaction of D'zalsya Cosmetik in Marisa District, Pohuwato Regency. The coefficient of determination (R2) shows that the contribution of 0.266 (26.6%) of purchase satisfaction is influenced by promotion and service quality while the remaining 0.73.4 (73.4%) is the contribution of other factors not examined in this study.